Carbon coated piezoresistive fiber sensors: From process monitoring to structural health monitoring of composites – A review. (February 2021) - Irfan, M.S.; Khan, T.; Hussain, T.; Liao, K.; Umer, R.
Abstract: Carbon nanomaterial-coated piezoresistive fiber sensors are finding applications in many industries for in-situ process and structural health monitoring of composites. These nanomaterials are embedded within the composite in two different ways; either by incorporating them in the matrix, or by depositing them on fibrous reinforcements. This review highlights the utility of carbon nanomaterials as deposition materials for fiber reinforcements and turning them into sensors for process monitoring during manufacturing and structural health monitoring during in-service life. A number of different strategies to coat carbon nanomaterials on fiber reinforcements are also discussed. A review of various monitored parameters during composites manufacturing such as reinforcement compaction response, flow-front tracking, and resin gelation and cure, as well as damage detection of finished composites using nanomaterial-coated in-situ sensors is also presented. Finally, current and future challenges are discussed where new types of 2D materials and their hybrids for next generation smart sensors are highlighted.